PENGUATAN KHIDMAH SANTRI MELALUI PENDAMPINGAN BERBASIS NILAI - Lutvi Ajizah; Hariyanto Hariyanto (LP2M Universitas Ibrahimy, 2022)
This activity is an activity whose orientation is community service. This activity is carried out as an implementation and reflection of the material obtained during education. In the process, community involvement in the implementation of activities becomes a must as a form of optimization in providing assistance, empowerment and strengthening on aspects of the topics or themes of assistance provided. Formation of student values through the Community Service Program at the Nurul Haromain Islamic Boarding School with the aim that the proclaimed character education can be carried out in formal institutions that are integrated with pesantren education.